Foreign Trade in the Kingdom of Lesser Armenia1099-1375 AD / 777-493 AH - جوني وفاء; حسن غادة; ونوس عامر (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
Trade in the Kingdom of Lesser Armenia flourished widely due to its strategic location on the eastern shores of the Mediterranean. The Kingdom overlooked the trade routes that connected Central Asia and the Persian Gulf with Europe, which made it occupy an important role in the trade of spices, livestock, leather, wool, cotton, wood, grain, wine, raisins, raw silk and other commodities that crossed the Kingdom of Lesser Armenia. This led to a major recovery in the Kingdom’s economy due to the fiscal duties it imposed on these transit goods. Moreover, what contributed to the advancement of trade in the Kingdom as well were the treaties concluded by the kings of Lesser Armenia with France, Catalonia, Sicily, the Republics of Italy, and other countries of the West, which helped the emergence of commercial societies and European colonies in the Kingdom with their churches, legal courts, and their commercial centers, as well as for the transformation of the Kingdom’s ports, such as Ayas Port and Gregory Port, into vital points and vast markets for merchants of the East and the West, be it Christian or Muslim.